Differences in gait parameters between children with achondroplasia and an age-matched control group of typically developed children in the age range of 6 to 12 years - Mareike Hergenröther; Katja Palm; Klaus Mohnike; Kerstin Witte (PLoS ONE, 2025)
For people with achondroplasia, the ability to walk pain-free and longer distances is essential for maintaining independence and quality of life. However, due to shorter extremities and misalignments in the lower limbs, the walking pattern of this cohort is often affected. One possible contributing factor is an imbalanced foot-to-leg ratio. Although these structural differences are well documented, research on their specific impact on gait mechanics remains limited. In particular, no studies have investigated how an imbalanced foot-to-leg ratio, among other potential factors, may influence kinematic and kinetic parameters throughout the gait cycle. Therefore, this study examined gait differences between children with achondroplasia (N = 15) and an age-matched (6–12 y) control group (N = 15). Using a 3D motion capture system (Vicon, 13 cameras) and a modified Plug-in-Gait model, spatio-temporal, kinematic, and kinetic parameters were analyzed. Statistical parametric mapping was applied to identify key moments in the gait cycle where significant deviations occurred between the two cohorts. Results showed that all spatio-temporal parameters, except cadence, differed significantly between the groups (p < 0.05). Most kinematic and kinetic parameters also showed significant differences, particularly around initial contact and toe-off. Notably, kinematic deviations were found at the pelvis, hip, and ankle during initial contact. Around toe-off, ankle kinematics were significantly different (p = 0.006). Kinetic differences at the hip and knee in both planes were also evident around toe-off. These findings suggest that an imbalanced foot-to-leg ratio may influence gait patterns, particularly during initial contact and toe-off phases. However, additional factors contributing to these deviations remain to be identified. Further research is necessary to elucidate these influences, which could support the development of more targeted and individualized therapeutic interventions for individuals with ACH.